Real single-channel color image encryption method based on computational ghost imaging. (1st December 2022) - Bai, Xing; Li, Jinxi; Yu, Zhan; Yang, Zhongzhuo; Wang, Yujie; Chen, Xingyu; Yuan, Sheng; Zhou, Xin
Abstract: A real single-channel color image encryption method based on computational ghost imaging is proposed. Compared with the currently proposed color single-channel encryption scheme, the method does not decompose the color image into three gray-scale images or encode it into a grayscale image for encryption. Instead, the color speckle patterns are used as the key to directly encrypt. The ciphertext is a grayscale image and thus has camouflage properties to a certain extent. Furthermore, the optical encryption setup is easy to be implemented and the key is generated by a chaotic system, which not only guarantees security but also reduces the volume of key transmission. The feasibility and high security of this method are supported by both computer simulations and optical experiments.